A schiff base-derived copper (II) complex is a potent inducer of apoptosis in colon cancer cells by activating the intrinsic pathway - Hajrezaie, M.; Paydar, M.; Moghadamtousi, S.Z.; Hassandarvish, P.; Gwaram, N.S.; Zahedifard, M.; Rouhollah, E.; Karimian, H.; Looi, C.Y.; Ali, H.M.; Majid, N.A.; Abdulla, M.A. (Hindawi Publishing Corporation, 2014)
Metal-based drugs with extensive clinical applications hold great promise for the development of cancer chemotherapeutic agents. In the last few decades, Schiff bases and their complexes have become well known for their extensive biological potential. In the present study, we examined the antiproliferative effect of a copper (II) complex on HT-29 colon cancer cells. The Cu(BrHAP)2 Schiff base compound demonstrated a potent tiproliferative effect in HT-29 cells, with an IC50 value of 2.87